Artificially intelligent law (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
This paper explores a series of thought experiments that postulate the ex-istence of "artificially intelligent law." An artificially-intelligent legal system is de-fined as one with three functional capacities: 1. The system has the capacity to gen-erate legal norms. 2. The system has the capacity to apply the legal norms that it generates. 3. The system has the capacity to use deep learning to modify the legal norms that it generates. The paper then considers the question whether such a sys-tem would be desirable as a matter of legitimacy and justice. The core idea of the paper is that the key to the evaluation of artificially intelligent law is to focus on the functional capacities of the system in comparison to comparable human systems, such as regulatory agencies.
Keywords: Artificial intelligence; expert legal systems; legitimacy; justice; our robot overlords